Genome-Wide Identification of mRNAs, lncRNAs, and Proteins, and Their Relationship With Sheep Fecundity - Wang, Chunxin; Zhao, Yunhui; Yuan, ZhiYu; Wu, Yujin; Zhao, Zhuo; Wu, Cuiling; Hou, Jian; Zhang, Mingxin (Frontiers in Genetics, 2022)
The exploration of multiple birth related genes has always been a significant focus in sheep breeding. This study aimed to find more genes and proteins related to the litter size in sheep. Ovarian specimens of Small Tail Han sheep (multiple births) and Xinji Fine Wool sheep (singleton) were collected during the natural oestrus cycle. Transcriptome and proteome of ovarian specimens were analyzed. The transcriptome results showed that “steroid hormone biosynthesis” and “ovarian steroidogenesis” were significantly enriched, in which HSD17B1 played an important role. The proteome data also confirmed that the differentially expressed proteins (DEPs) were enriched in the ovarian steroidogenesis pathway and the CYP17A1 was the candidate DEP. Further, lncRNA MSTRG.28645 was highly expressed in Small Tailed Han sheep but lowly expressed in Xinji fine wool sheep. In addition, MSTRG.28645, a hub gene in the co-expression network between mRNAs and lncRNAs, was selected as one of the candidate genes for subsequent verification. Expectedly, the over-expression and interference of HSD17B1 and MSTRG.28645 showed a significant effect on hormone secretion in granulosa cells. Therefore, this study confirmed that HSD17B1 and MSTRG.28645 might be potential genes related to the fecundity of sheep. It was concluded that both HSD17B1 and MSTRG.28645 were critical regulators in the secretion of hormones that affect sheep's fecundity.